Risk and return under Shari'a framework: An attempt to develop Shari'a compliant asset pricing model (SCAPM) - Muhammad Hanif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
A speedy emerging area of finance is the Shari'a compliant financial system. In first decade of 21st century Islamic financing has shown tremendous increase and global volume has reached to US 1,041 billion by the end of 2009. Being financial intermediaries Islamic Financial Institutions (IFIs) have shown commendable progress in deposit collection under profit and loss sharing schemes however investment avenues are limited in comparison of conventional banks. Although a large number of financing modes are available to IFIs, yet maintenance of required liquidity is serious issue because money market and capital market is dominated by interest based instruments and conventional practices (some are clearly prohibited by Shari'a). Recently Al-meezan Investment Management Ltd. (AIML) has started screening of Shari'a compliant stocks on KSE, and provided an avenue for Shari'a Compliant Investors/IFIs to invest in equities. This study is conducted to understand conventional asset pricing models, document any mismatching with Shari'a financial system, and suggest amendments if required. Findings suggest existing models of equity pricing (CAPM, APT/MFM) are very much practicable under Shari'a framework with slight modification of risk free return because under Shari'a frame work risk free returns do not exist.
Keywords: 330; SCAPM; Islamic financing; APT; Security pricing; valuation; Spekulation; Islam; Pakistan; CAPM; Theorie